The Association of Health Literacy With Preventable Emergency Department Visits: A Cross‐sectional Study. (14th August 2017) - Balakrishnan, Meenakshi P.; Herndon, Jill Boylston; Zhang, Jingnan; Payton, Thomas; Shuster, Jonathan; Carden, Donna L.
Abstract: Background: Policymakers argue that emergency department (ED) visits for conditions preventable with high‐quality outpatient care contribute to waste in the healthcare system. However, access to ambulatory care is uneven, especially for vulnerable populations like minorities, the poor, and those with limited health literacy. The impact of limited health literacy on ED visits that are preventable with timely, high‐quality ambulatory care is unknown. Objective: The objective was to determine the association of health literacy with preventable ED visits. Methods: We conducted an observational cross‐sectional study of potentially preventable ED visits (outcome) among adults (≥18 years old) in an ED serving an urban community. We assessed health literacy (predictor) through structured interviews with the Rapid Estimate of Adult Literacy in Medicine (REALM). We recorded age, sex, race, employment, payer, marital and health status, and number of comorbidities through structured interviews or electronic record review. We identified potentially preventable ED visits in the 2 years before the index ED visit by applying Agency for Healthcare Research and Quality technical specifications to identify ambulatory care sensitive conditions using ED discharge diagnoses in hospital administrative data. We used Poisson regression to evaluate the number of preventable ED visits among patients with limited (REALM < 61) versus adequate (REALM ≥ 61) health literacy after adjusting for covariates. Results: Of 1, 201 participants, 709 (59%) were female, 370 (31%) were African American, mean age was 41.6 years, and 394 (33%) had limited health literacy. Of 4, 444 total ED visits, 423 (9.5%) were potentially preventable. Of these, 260 (61%) resulted in hospital admission and 163 (39%) were treat and release. After covariates were adjusted for, patients with limited literacy had 2.3 (95% confidence interval [CI] = 1.7–3.1) times the number of potentially preventable ED visits resulting in hospital admission compared to individuals with adequate health literacy, 1.4 (95% CI = 1.0–2.0) times the number of treat‐and‐release visits, and 1.9 (95% CI = 1.5–2.4) times the number of total preventable ED visits. Conclusions: Our results suggest that the ED may be an important site to deploy universal literacy‐sensitive precautions and to test literacy‐sensitive interventions with the goal of reducing the burden of potentially preventable ED visits on patients and the healthcare system.